Implementation of digital-based discovery learning to improve motivation in science learning for fifth grade students - Muhammad Wahyu Hidayat; Yunita Sari; Muhammad Afandi (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2026)
The advancement of digital technology has created new opportunities in education, especially in enhancing student motivation. This study aimed to evaluate the effectiveness of a digital-based Discovery Learning model in teaching the properties of light in Natural Science (IPA) at the elementary level. A descriptive qualitative approach was employed, with data collected through classroom observation, interviews, and documentation. The participants consisted of 17 fifth-grade students, a classroom teacher, and the principal. Data were analysed qualitatively by comparing students’ learning motivation before and after the implementation of the model. Findings indicated a significant improvement in motivation. Student interest in the material increased from 59% to 100%, enthusiasm for participating in learning rose from 59% to 94%, and persistence in completing tasks improved from 53% to 88%. Key factors contributing to these gains included the use of educational videos, discussion-based experiments, and interactive quizzes via the Wordwall application. These results demonstrate that combining Discovery Learning with digital media effectively enhances motivation in science learning for elementary students. It is recommended that Wordwall be further developed with experimental simulation features and that teachers receive training to maximise the use of digital tools in classroom learning.